Are out-of-school adolescents at higher risk of adverse health outcomes?: evidence from 9 diverse settings in sub-Saharan Africa - De Neve, Jan-Walter; Karlsson, Omar; Canavan, Chelsey R.; Chukwu, Angela; Adu‐Afarwuah, Seth; Bukenya, Justine; Darling, Anne Marie; Harling, Guy; Moshabela, Mosa; Killewo, Japhet; Fink, Günther; Fawzi, Wafaie W.; et al. (Tropical medicine & international health, 2020)
Objectives We analysed mutually comparable surveys on adolescent attitudes and behaviours from nine sites in seven sub-Saharan African countries, to determine the relationship between school enrolment and adolescent health outcomes. Methods Data from the Africa Research, Implementation Science, and Education Network cross-sectional adolescent health surveys were used to examine the associations of current school enrolment, self-reported general health and four major adolescent health domains: (i) sexual and reproductive health; (ii) nutrition and non-communicable diseases; (iii) mental health, violence and injury; and (iv) healthcare utilisation. We used multivariable Poisson regression models to calculate relative risk ratios with 95% confidence intervals (CI), controlling for demographic and socio-economic characteristics. We assessed heterogeneity by gender and study site. Results Across 7829 adolescents aged 10-19, 70.5% were in school at the time of interview. In-school adolescents were 14.3% more likely (95% CI: 6-22) to report that their life is going well; 51.2% less likely (95% CI: 45-67) to report ever having had sexual intercourse; 32.6% more likely (95% CI: 9-61) to report unmet need for health care; and 30.1% less likely (95% CI: 15-43) to report having visited a traditional healer. School enrolment was not significantly associated with malnutrition, low mood, violence or injury. Substantial heterogeneity was identified between genders for sexual and reproductive health, and in-school adolescents were particularly less likely to report adverse health outcomes in settings with high average school enrolment. Conclusions School enrolment is strongly associated with sexual and reproductive health and healthcare utilisation outcomes across nine sites in sub-Saharan Africa. Keeping adolescents in school may improve key health outcomes, something that can be explored through future longitudinal, mixed-methods, and (quasi-)experimental studies.